Assessment of Alaska reindeer populations and range conditions - Swanson, J. D.; Barker, M. H. W. (Rangifer, 1992)
Populations of reindeer (Rangifer tarandus) have fluctated greatly since their introduction to Alaska in 1891. In the 1930s, reported numbers exceeded 600 000. Presently, 38 000 reindeer graze 6.2 million ha of rangeland and woodland in Western Alaska (from 66°54’N to 52°07’N latitude). Condition of winter range producing fruticose lichens (Cladina rangiferina, Cladina arbuscula, Cladina stellaris, Cetraria cucullata, Cetraria islandica) is of major concern. Monitoring programs have been established for vegetation, fire, reindeer and wildlife. Reindeer have overgrazed lichen resources on some Bering Sea Islands. Wildfires have had the greatest impact on lichen range depletion on the mainland. Overgrazing has been a problem in localized areas. Moose (Alces alces) and muskox (Ovibos moschatus) rarely contribute to major lichen depletion. 60-80% of the mainland and 5-30% of most island winter lichen ranges are presently estimated to be in good to excellent ecological condition. Procedures for assessing condition of the lichen ranges are being further refined.